Cultural interaction and value pursuit: the Shijing in German culture - Yang Xinwen (Language and Semiotic Studies)
In addition to being a treasure of Chinese literature, the Shijing is also an integral part of world literature. Its translation and dissemination in Germany have a history of nearly 300 years, reflecting Germany’s sustained attention to Chinese literary classics and highlighting the dialogue and interactions between the two cultures at different historical stages. The powerful textual interpretations and meaning-construction functions of the Shijing are key reasons for its enduring relevance in Germany. From Jakobson’s theory of translation semiotics, the interlingual translation of the Shijing into German can be divided into a direct symbolic conversion from Chinese to German and translation via a third language. Versions directly based on the original Chinese text undergo a process from intralingual translation to interlingual translation, ultimately achieving equivalence in difference between Chinese and German language and cultural information as distinct symbolic systems. German translators and scholars have approached the Shijing from the perspectives of cultural interpretation, literary criticism, and aesthetic analysis, conducting cross-cultural interpretations. Embedded within this are diverse value propositions based on local cultural and academic traditions, including promoting cultural understanding, embodying the Chinese imagination, shaping literary concepts, and fostering cultural exchange. Investigating the cultural interaction during the dissemination of the Shijing in Germany and the research value propositions of German academia contributes to examining the construction of Shijing Studies in Europe and promotes the study of the Chinese classics’ dissemination overseas.